Electrophile induced branching cascade: a powerful approach to access various molecular scaffolds and their exploration as novel anti-mycobacterial agents - Patil, Nitin T.; Konala, Ashok; Sravanti, Sudha; Singh, Ashita; Ummanni, Ramesh; Sridhar, Balasubramanian (Chemical Communications, 2013)
Herein we report on the Electrophile Induced Branching Cascade (EIBC), a new technique to produce a variety of biologically important molecular scaffolds. Some compounds exhibit excellent activities against Mycobacterium smegmatis.

When gold meets chiral bronsted acid catalysts: extending the boundaries of enantioselective gold catalysis - Inamdar, Suleman M.; Konala, Ashok; Patil, Nitin T. (Chemical Communications, 2014)
This review describes the development in the use of Au(I)/Bronsted acid binary catalytic systems to enable an enantioselective transformation in one-pot that cannot be achieved by gold catalysts alone. The examples discussed herein are promising since apart from using chiral ligands there exists a possibility of using chiral Bronsted acids. Clearly, the horizon for enantioselective gold catalysis has been expanded as more options to make the gold-catalyzed reactions enantioselective have become available.